Ocellar structure and neural innervation in the honeybee - Yu-Shan eHung; Michael Robert Ibbotson (Frontiers Media S.A., 2014)
Honeybees have a visual system composed of three ocelli (simple eyes) located on the top of the head, in addition to two large compound eyes. Although experiments have been conducted to investigate the role of the ocelli within the visual system, their optical characteristics, and function remain controversial. In this study, we created three-dimensional (3-D) reconstructions of the honeybee ocelli, conducted optical measurements and filled ocellar descending neurons to assist in determining the role of ocelli in honeybees. In both the median and lateral ocelli, the ocellar retinas can be divided into dorsal and ventral parts. Using the 3-D model we were able to assess the viewing angles of the retinas. The dorsal retinas view the horizon while the ventral retinas view the sky, suggesting quite different roles in attitude control. We used the hanging drop technique to assess the spatial resolution of each retina. The lateral ocelli have considerably higher spatial resolution compared to the median ocellus. Moreover, in both types of ocellus the dorsal retina has a higher spatial resolution than the ventral retina. In addition, we established which ocellar retinas provide the input to five pairs of large ocellar descending neurons. We found that four of the neuron pairs had their dendritic fields in the dorsal retinas of the lateral ocelli, while the fifth had fine dendrites in the ventral retina. One of the neuron pairs also sent very fine dendrites into the border region between the dorsal and ventral retinas of the median ocellus.